2019
DOI: 10.1155/2019/1832152
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Antiretroviral Therapy (ART) Initiation among Hospitalized Adults in a Resource-Limited Settings: A Challenge to the Global Target of ART for 90% of HIV-Infected Individuals

Abstract: Background. Combination antiretroviral therapy (cART) initiation in hospital settings, where individuals often present with undiagnosed, untreated, advanced HIV disease, is not well understood. Methods. A cross-sectional study was conducted to determine a period prevalence of cART initiation within two weeks of eligibility, as determined at hospitalization. Using a pretested and precoded data extraction tool, data on cART initiation status and reason for not initiating cART was collected. Phone calls were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 26 publications
2
25
1
Order By: Relevance
“…The current study demonstrated poor adherence is also a significant predictor of mortality. Our result is consistent with the results of studies done in Debre Markos, 21 in southwest Ethiopia 23 and in Uganda 15 , 16 which may be explained by the fact that clients who have poor adherence are at risk of developing resistance to medication and lastly treatment failure which can lead to mortality if it does not detect early.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The current study demonstrated poor adherence is also a significant predictor of mortality. Our result is consistent with the results of studies done in Debre Markos, 21 in southwest Ethiopia 23 and in Uganda 15 , 16 which may be explained by the fact that clients who have poor adherence are at risk of developing resistance to medication and lastly treatment failure which can lead to mortality if it does not detect early.…”
Section: Discussionsupporting
confidence: 92%
“…It might be since during the time before the test and treat the clients were not eligible for treatment until they have advanced disease and low CD4, so that they may have not responded well to treatment which results in the death of many clients due to immune reconstitution syndrome IRIS. 16,17 The effect of the test and treat strategy found by this study is in line with the studies done in the Gurage zone in Ethiopia 18 and South Africa, 1 but in a study done in Nigeria, the mortality rate after implementation of test and treat was 2%, 17 which was much less than our finding 13.4%. This may happen despite the implementation of the test and treat strategy because clients are still presenting for care and treatment late as evidenced by 22% of clients in the test and treat cohort who presented with CD4 lower than 200cells/cubic mm and 28% who presented with WHO stages III and IV at baseline.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, about 75% of HIV-infected patients delayed ART initiation and had 33% pre-ART mortality rate because of HIV-related OIs [15]. Different studies done in Sub-Saharan Africa showed that still there is a high prevalence of OIs among HIV-infected patients taking ART [16,17].…”
Section: Introductionmentioning
confidence: 99%